Strategi Pemberdayaan UMKM Kebab Kenzatha - Indah Rahma Wati; Tasya Afriza Cahyani; Zahwa Saviola Ramadhini (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study aims to describe the empowerment strategy of Micro, Small, and Medium Enterprises (MSMEs) implemented by the Kebab Kenzatha MSME operating in Bukittinggi City. The background of this study is based on the important role of MSMEs in driving the local economy, particularly in creating jobs, increasing community income, and strengthening the domestic economic structure. MSME empowerment is a vital strategy in ensuring the sustainability and competitiveness of small and medium enterprises amidst increasingly competitive market competition. There are various dimensions in MSME empowerment, such as strengthening the capacity of individual business actors, increasing access to markets, access to capital, utilization of technology, and adequate policy or institutional support. This study uses a descriptive qualitative approach. This method was chosen because it is considered most appropriate to comprehensively and objectively describe the various empowerment strategies that have been or are being implemented by MSME actors, particularly Kebab Kenzatha. Through observation and in-depth interviews with MSME owners, researchers obtained information about business activities and marketing strategies implemented. Based on the results of observations, it is known that the Kebab Kenzatha MSME is still managed independently by its owner without the involvement of employees or additional labor. This indicates that its organizational structure is still very simple. Meanwhile, in terms of marketing strategy, this MSME utilizes its closest social networks, such as friends of the business owner and students at Campus V of Padang State University (UNP), as its primary target market. This approach reflects a marketing strategy based on social relationships and word-of-mouth promotion, commonly employed by MSMEs with limited resources. Therefore, the empowerment of the Kebab Kenzatha MSME is still in its early stages and requires further support for optimal long-term development.